Survivors of veno-arterial membrane oxygenation have good long-term quality of life. Issue 10 (October 2022) - North, Monique; Samara, Michael; Eckman, Peter M; Bennett, Mosi; Schmidt, Christian; Garberich, Ross; Hryniewicz, Katarzyna
Veno-arterial extracorporeal membrane oxygenation (VA ECMO) is used for the management of acute cardiogenic shock with improving short term survival. However, the long-term quality of life (QOL) of this patient population is not well characterized. We prospectively evaluated the QOL of adult patients who survived VA ECMO support for cardiogenic shock at our institution between October 2011 and January 2018 with the Minnesota Living with Heart Failure Questionnaire (MLWHFQ). We surveyed survivors at 3, 6, and 9 months after discharge, and annually for up to 5 years thereafter. A total of 64 patients were evaluated: mean age 54 ± 13 years, 73% male. There were 178 total surveys completed. MLWHFQ total scores significantly improved over time and this pattern was sustained (51.7 ± 25.3 at 3 months, vs 37.7 ± 23.6 at 6 months, vs 25.4 ± 21.3 at ⩾9 months ( p < 0.01, p -trend < 0.01)). Most patients supported with VA ECMO for cardiogenic shock who survive to discharge demonstrate excellent quality of life, 6 months since index hospitalization, which is maintained over subsequent years.